Reanalysis of Chinese Treponema pallidum samples: all Chinese samples cluster with SS14-like group of syphilis-causing treponemes - Strouhal, Michal; Oppelt, Jan; Mikalová, Lenka; Arora, Natasha; Nieselt, Kay; González-Candelas, Fernando; Šmajs, David (BMC research notes, 2018)
OBJECTIVE: Treponema pallidum subsp. pallidum (TPA) is the causative agent of syphilis. Genetic analyses of TPA reference strains and human clinical isolates have revealed two genetically distinct groups of syphilis-causing treponemes, called Nichols-like and SS14-like groups. So far, no genetic intermediates, i.e. strains containing a mixed pattern of Nichols-like and SS14-like genomic sequences, have been identified. Recently, Sun et al. (Oncotarget 2016. https://doi.org/10.18632/oncotarget.10154 ) described a new "phylogenetic group" (called Lineage 2) among Chinese TPA strains. This lineage exhibited a "mosaic genomic structure" of Nichols-like and SS14-like lineages. RESULTS: We reanalyzed the primary sequencing data (Project Number PRJNA305961) from the Sun et al. publication with respect to the molecular basis of Lineage 2. While Sun et al. based the analysis on several selected genomic single nucleotide variants (SNVs) and a subset of highly variable but phylogenetically poorly informative genes, which may confound the phylogenetic analysis, our reanalysis primarily focused on a complete set of whole genomic SNVs. Based on our reanalysis, only two separate TPA clusters were identified: one consisted of Nichols-like TPA strains, the other was formed by the SS14-like TPA strains, including all Chinese strains.
Keywords: Sequence Analysis, DNA; Syphilis; Humans; Phylogeny; lidé; Treponema pallidum; Genome, Bacterial; sekvenční analýza DNA; Polymorphism, Single Nucleotide; fylogeneze; Single nucleotide variant; Phylogenetic analysis; genom bakteriální; Genome sequencing; China; Čína; jednonukleotidový polymorfismus